Combination of Telerehabilitation with Conventional Therapy in the Treatment of Bilateral Carpal Tunnel Syndrome: A Case Report - Wico Hartantri; Lydia Arfianti (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
Carpal Tunnel Syndrome (CTS) is the most common entrapment neuropathy of median nerve. The current development of global COVID-19 pandemic urges medical rehabilitation services to deliver a comprehensive approach amidst the physical distancing period. This case report aims to investigate the feasibility and efficacy of implementing telerehabilitation to the conventional therapy in the treatment of CTS. A 51-year old female presented with post carpal tunnel release of the left hand, and chronic-severe CTS on right hand. We maintained 5 weeks rehabilitation programs of combined telerehabilitation and face-to-face rehabilitation therapy and evaluation. The patient showed good compliance with the programs and achieved the intended goals within 5 weeks of therapy. Patient showed improvement (in pain, range of motions, hand functions, and ADLs). Telerehabilitation combined with conventional therapy were effective and feasible in treating patient with bilateral (left post-release and right chronic-severe) CTS. The use of telerehabilitation may add accessibility while reducing physical contact in order to minimize the risk of transmission of COVID-19.